Correlação entre morfologia, percolação elétrica e propriedades mecânicas de compósitos da blenda PLA/PBS com grafite expandido - Sousa, Daniel Eurico Salvador de (2013)
In recent years, researchers from industry and universities have focused their interests in polymer nanocomposites, especially in multifunctional composites. The composites made from nano expanded graphite ( nGE ) can provide to the polymer matrix an innovative balance of structural, electrical and thermal conductivity, electromagnetic shielding and improved barrier and wear resistance properties. The increasing demand of using biodegradable polymers, such as poly (lactic acid ) (PLA ) and its blends with poly ( butylene succinate) (PBS), in packages of short lifespan with low resistivity requirements, motivated this work. Nanocomposites of nGE with PLA and PLA / PBS blends were evaluated on the effects of conductive nanofiller content and processing methods in their rheological, mechanical, and electrical properties, in order to correlate and possibly control the formation of the percolation network. The nanographite had a major mechanical reinforcement effect in of the composite with PLA / PBS, increasing all tensile properties. Through microstructural analysis, it was was observed the selective localization of graphite particles in PLA, forming a percolated co-continuous phase with PBS phase. This phenomenon was identified as double percolation, result of the preferential nGE gelation in PLA by the processes of coalescence of PBS and possible crystallization of polymers in the blend. The PLA composites remained resistive, since the nGE particles homogeneous dispersion was maintained. The lowest resistivities were found in the samples of the blend processed by compression moulding, more favorable process for the formation of the electrical percolation network through the mechanisms mentioned above. The coalescence of PBS phase proved to be determinant for the electrical percolation.